Experimental examination of the “energy upconversion” theory for green plant photosynthesis - Warden, Joseph T. (1976)
Spinach chloroplasts, dark adapted for periods of three days to three months, yield P700(+) formation (electron spin resonance signal 1) on the first as well as the following flashes in an actinic series of xenon light flashes of 10 μs duration. These data are in contradiction with the prediction of the “energy upconversion” theory [F. K. Fong (1975) Appl. Phys. 6, 151-156] that only the second flash would be effective.